2016
DOI: 10.1186/s12978-016-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Supportive supervision for volunteers to deliver reproductive health education: a cluster randomized trial

Abstract: BackgroundCommunity Health Volunteers (CHVs) can be effective in improving pregnancy and newborn outcomes through community education. Inadequate supervision of CHVs, whether due to poor planning, irregular visits, or ineffective supervisory methods, is, however, recognized as a weakness in many programs. There has been little research on best practice supervisory or accompaniment models.MethodsFrom March 2014 to February 2015 a proof of concept study was conducted to compare training alone versus training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Individual, group, and program factors have each been shown to influence the performance of CHVs (1, 3, 5, 6, 815, 1719, 25). Factors previously reported to result into improved performance include the female gender, regular supervision and provision of feedback, higher education, the availability of job aides and other tools, and feeling “connected” with the system (3, 5, 6, 911, 13, 14, 17, 18). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual, group, and program factors have each been shown to influence the performance of CHVs (1, 3, 5, 6, 815, 1719, 25). Factors previously reported to result into improved performance include the female gender, regular supervision and provision of feedback, higher education, the availability of job aides and other tools, and feeling “connected” with the system (3, 5, 6, 911, 13, 14, 17, 18). …”
Section: Discussionmentioning
confidence: 99%
“…Implementation mechanisms in the country have varied and have been largely steered by government partners, including local and foreign non-governmental organizations, as government funding and resources have dwindled since inception (7). Some of the factors described to improve their performance include support from the community and health facilities, adequate work resources, regular feedback, and supervision (3, 6, 11, 13, 17, 18). Challenges have been attributed to lack of or low remuneration, lack of uniform and regular contact with supervisors, or lack of motivation, high workload, and inadequate skills (3, 12).…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Research on CHWs in other contexts has also supported innovations in CHW supervision going beyond their facility-based supervisors [27][28][29]. MANIFEST also found that non-monetary incentives such as T-shirts, certificates and musawo (doctor) status in the community motivated VHTs to continue working.…”
Section: Strengthening Chwsmentioning
confidence: 97%
“…Based on MMAT, eight studies scored 100% [14][15][16][17][18][19][20][21]; ten studies scored 75% [22][23][24][25][26][27][28][29][30][31] and two studies scored 50% [6,32]. With an average MMAT score of 82.5% across the included studies, the studies are considered to be of high quality.…”
Section: Quality Appraisalmentioning
confidence: 99%